Design optimization of permanent magnet synchronous motor for automated ground vehicles - Tan, Joshua Yong Hao (Nanyang Technological University, 2024)
With the increasing demand for automation in the current 4.0 Industrial Revolution, the interest and demand for Permanent Magnet Synchronous Motors (PMSM) are gaining traction in many applications due to their small size, high torque, high efficiency, and performance. This study presents the design optimization of Permanent Magnet Synchronous Motors (PMSM) specifically for Automated Ground Vehicles (AGVs) will be presented in this report. This project’s focus will be on the rotor pole optimization to increase efficiency and torque density. By using a 12-slot, 10 pole PMSM Motor as the main design, employing Finite Element Method (FEM) analysis through JMAG software, different conditions, and parameters will be analysed and compared to find the most optimal design to be used for AGVs. The primary objective was to enhance motor performance, focusing on reducing torque ripple and increasing average torque, therefore proposing a superior alternative to traditional geared-drive systems which are prevalent in the current industry. Through various meticulous geometric design modifications, optimal material selection, and precise current density settings, significant improvements were eventually achieved in terms of the motor’s different performance indicators. The optimized PMSM design demonstrated a considerable reduction in torque ripple and an increase in average torque, indicating a notable enhancement and progress in research for PMSMs to be efficient and dependable for AGVs and their applications. The reasoning and the analysis behind the proposed changes in parameters and conditions will be delivered and discussed in this report. In addition to showcasing the potential of multi-pole surface mounted PMSMs, this project also highlights the effective use of modern engineering tools like JMAG for sophisticated motor design and optimization tasks. The final findings of this project can attest to the crucial role of advanced PMSMs in the future application of AGVs, suggesting a pivot towards a more sustainable tomorrow.